Joint adaptive modulation adaptive beamforming for mobile transmissions - Ibrahim, S. A.; Alias, M. Y.; Ahmad, N. N. (IEEE Xplore, 2007)
Spectrally efficient techniques such as adaptive beamforming (ABF) and adaptive modulation (AM) are two powerful methods to increase the capacity of mobile systems. Adaptive beamforming exploits the spatial knowledge from antenna arrays in suppressing co-channel interference. On the other hand, adaptive modulation maximizes the throughput while maintaining a given target bit error rate (BER) by selecting the modulation mode according to the instantaneous channel quality. In order to maximize the benefits from both techniques, their combination is considered. The simulation of fixed modulation adaptive beamforming (FM-ABF) shows that the degradation in BER is reasonably small even for a large reduction in weight recalculation rate. This motivates the investigation of joint adaptive modulation adaptive beamforming (AM-ABF) system, where adaptive modulator assists adaptive beamformer in determining the need to recalculate the weight. The novelty of this paper lies in the ability of the joint technique to adapt the weight recalculation rate according to the near instantaneous signal-to-interference-plus-noise ratio (SINR), which represents the channel fading rate. Simulation results are shown to compare the performance of the proposed joint AM-ABF with the FM-ABF for the case of one and two interferers. Results for both cases show that the proposed AM-ABF is able to fulfill the target BER <= 10(-2), while improves the performance by reducing the required average received SINR as compared to the FM-ABF technique, with the improvement of up to 10 dB at BER of 1 x 10(-2). In terms of average bits-per-symbol (BPS) throughput, the joint AM-ABF outperforms FM-ABF at the average received SINR of more than 24 dB and 26 dB for single interferer and two interferers, respectively.